A leitura e a escrita como prática religiosa: um estudo de caso sobre crianças e adultos pertencentes à Igreja Metodista - Almeida, Fabio Fetz de (2009)
The research examined the influence of the religious practices of the Methodist Church and its Sunday School on the process of literacy, in the year 2008. Through a case study involving the techniques of observation, two families were selected for a detailed study. The instruments used to develop this research was semi-structured interviews, the observation of the religious cult and the Sunday School practices development in the weekends, and the analysis of the pedagogical material used in the Sunday School. The objective was to observe the practices of literacy to which children and adults were exposed. The following hypothesis guided the research: the learning practices of the Sunday School and the family relationship, although based on the religion dogmas, involves literacy exercises that encourage the development of skills of writing in children. The study group was composed by two children in school age (between ten and thirteen years old) and their families. The reading and writing practices of the select families was analyzed through the concepts of habitus and cultural capital (Bourdieu, 2007) and family configuration (Lahire, 2004). It was observed that the investigated religious field has solid social values that contribute positively to the learning process of the younglings through the social practices development in the Sunday School. Thus, the embodiment of cultural capital as habitus and the ways of production of symbolic goods in the religious field has contribute to the development of writing, reading and interpretation skills of the select group